The Online Learning of Teacher Profession Education Program (PPG) for In-service English Teachers: Challenges and Accelerated Learning Factors - Utami, IGA Lokita Purnamika (Jurnal Pendidikan Indonesia, 2018)
The Indonesian government has currently implemented a hybrid learning program for in-service teachers who want to enroll in the Teacher Profession Education program (locally known as Pendidikan Profesi Guru). This Case study aimed to identify English teachers' perceptions on the challenges and accelerated-learning factors of online learning. 15 English teachers who were the participants of the said program hosted by Universitas Pendidikan Ganesha and 2 English mentors were the participants of the study. The informal interview was the main data collection technique which was transcribed verbatim and content analyzed. The participants of the study perceived 4 challenges of online learning, such as participants' lack of ICT skills, the incompleteness of the uploaded modules, instructors' unfamiliarity with the learning software, and the excessive assignments to be finished in limited time. There were 4 factors considered to accelerate teacher's learning: the mentor factor, the participant factor, the managerial factor, and the facility factor.